Early fate bias in neuroepithelial progenitors of hippocampal neurogenesis. Issue 4 (5th December 2022) - von Berlin, Leonie; Westholm, Jakub Orzechowski; Ratz, Michael; Frisén, Jonas
Abstract: Hippocampal adult neural stem cells emerge from progeny of the neuroepithelial lineage during murine brain development. Hippocampus development is increasingly well understood. However, the clonal relationships between early neuroepithelial stem cells and postnatal neurogenic cells remain unclear, especially at the single‐cell level. Here we report fate bias and gene expression programs in thousands of clonally related cells in the juvenile hippocampus based on single‐cell RNA‐seq of barcoded clones. We find evidence for early fate restriction of neuroepithelial stem cells to either neurogenic progenitor cells of the dentate gyrus region or oligodendrogenic, non‐neurogenic fate supplying cells for other hippocampal regions including gray matter areas and the Cornu ammonis region 1/3. Our study provides new insights into the phenomenon of early fate restriction guiding the development of postnatal hippocampal neurogenesis.